Modal Sosial dan Sponsor Karier Pengaruhnya terhadap Kesuksesan Karier Manajer - Kistyanto, Anang (Jurnal Aplikasi Manajemen, 2008)
This research aimed in explaining the influence of social capital on the career success with career sponsorship as the intervening variable. Using two stage sampling, the 232 questionnaires were distributed to the manager of state-owned companies (BUMN) at East Java and 108 of the questioner were returned. The result of the SEM appeared that the managers having better social capital would have better career sponsorship where they would has career support, challenge job, career protection, career coaching, technical mentoring and advice, office political coaching, and better spiritual coaching. This research discovered that trust dimension was the weakest dimension in forming social capital. In the variable of social capital, connection dimension was the strongest dimension in forming social capital variable. In the career sponsorship variable, the strongest indicator in forming career sponsorship career was technical mentoring and advice, while the weakest indicator in forming the career sponsorship variable was career protection.